A Comparative Strategy Using PI & Fuzzy Controller for Optimization of Power Quality Control - Garima Sinha; Pankaj Kumar Goswami; Sudhir Kumar Sharma (IAES Indonesian Section, 2018)
This paper explores the analytical study and simulation of fuzzy logic controller and PI controller, to control the dc output voltage of shunt active power filter for harmonic reduction and power quality improvement in case of nonlinear load. Here we have exercised an effort to design and evaluate a converter to compensate the harmonics for 1-phase AC to DC bridge rectifier which is working as the main converter in unregulated mode. The work depends on the scheme where an ancillary converter is linked in shunt with the main or primary converter whose turn on and turn off time is controlled by an appropriate controller (pi/fuzzy logic) for harmonic compensation of the primary converter which is working as nonlinear load. The Model of converter is proposed on MATLABSoftware and the results are analyzed satisfactorily.